Interpretable Machine Learning untuk Prediksi Penempatan Kerja: Analisis Fitur Berbasis SHAP - Swono Sibagariang (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2025)
Predictive modeling is important in analyzing graduates’ job outcomes, especially in forecasting job placements based on academic performance and courses. This study aims to improve predictive accuracy and interpretability in job placement classification using advanced machine learning models and SHapley Additive exPlanations (SHAP) analysis. Utilizing a dataset containing graduates’ academic records, including course grades, grade point average (GPA), and internship duration, this research employed several classification models, including decision tree, random forest, extreme gradient boosting (XGBoost), light gradient-boosting machine (LightGBM), CatBoost, and logistic regression. Evaluation metrics showed that most models achieve 92% precision, 92% recall, and 92% F1 score, with an accuracy of 85%, while logistic regression excelled with 100% recall, 96% F1 score, and 92% accuracy. SHAP analysis identified key features such as Administration, Computer Organization, Information Systems, Entrepreneurship, Professional Ethics, and Web Programming as the most influential in predicting job placement. Other significant contributors include Introduction to Information Technology, Software Engineering II, and Data Mining, although with relatively lower influence. Extracurricular activities and internship experiences were also found to be influential factors, highlighting the importance of academic and nonacademic elements in shaping graduates’ career prospects. These findings highlight and emphasize the need to provide students with certain academic courses to better prepare them for the job market. These findings emphasize the importance of interpretable machine learning models in career forecasting, enabling educational institutions to optimize curriculum design and enhance graduates’ employability. Future research should explore feature selection techniques, temporal analysis, and personalized recommendation systems to refine predictive accuracy.